Freehand drawing and discovery : urban sketching and concept drawing for designers - Richards, James, 1955- (Hoboken, New Jersey : Wiley, 2013)
Features access to video tutorials!Designed to help architects, planners, and landscape architects use freehand sketching to quickly and creatively generate design concepts, Freehand Drawing and Discovery uses an array of cross-disciplinary examples to help readers develop their drawing skills.
Includes index.
ARC
Keywords: Architectural drawing -- Technique; Cities and towns in art; Architecture